Diagnostic Accuracy of the Perinatal Anxiety Screening Scale (PASS) Against MINI-ICD-10: A Cross-Sectional Study Among Pregnant Women in Primary Care Settings, Indonesia - Suyuti, Sartika; Karuniawati, Nia; Magfirah, Andi; Sani, Andi (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2026)
Anxiety disorders during pregnancy are prevalent mental health concerns that can affect both maternal and fetal outcomes. Valid and reliable screening tools are essential for early detection and intervention. This study aimed to evaluate the diagnostic performance of the Perinatal Anxiety Screening Scale (PASS) compared to MINI-ICD 10 as the gold standard in detecting anxiety disorders among pregnant women. A cross-sectional diagnostic accuracy study was conducted at Kaluku Bodoa Community Health Center, Makassar City, from October to November 2025. Eighty pregnant women attending antenatal care were recruited using purposive sampling. Data were collected through structured interviews using PASS and MINI-ICD 10 questionnaires. Diagnostic accuracy measures including sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall accuracy were calculated. The prevalence of anxiety disorders was 36.25% (n=29) based on MINI-ICD 10 and 53.8% (n=43) based on PASS. The majority of participants were aged 21-35 years (80%), had completed senior high school education (53.8%), and were housewives (77.5%). Most were in their third trimester (67.5%) and nulliparous (43.8%). PASS demonstrated good diagnostic performance with sensitivity of 86.21%, specificity of 64.71%, PPV of 58.14%, NPV of 89.19%, and overall accuracy of 72.5%. PASS showed acceptable diagnostic performance as a screening tool for anxiety disorders in pregnant women, with high sensitivity making it suitable for initial screening in primary healthcare settings. However, the moderate specificity suggests that positive screening results should be confirmed with gold standard diagnostic interviews.